LA COLECCIÓN HIMENOPTEROLÓGICA (INSECTA) DEL MUSEO DE ZOOLOGÍA “ALFONSO L. HERRERA” DE LA FACULTAD DE CIENCIAS, UNAM, MÉXICO - Yáñez-Ordóñez, Olivia; Hinojosa-Díaz, Ismael (Instituto de Ecología, A.C., 2022)
The Hymenoptera collection of the Museo de Zoología “Alfonso L. Herrera”, Facultad de Ciencias, UNAM, has 22,015 bee specimens in a database, which belong to six families, 115 genera and 819 species and subspecies, and have been collected from 22 states in the country and 21 vegetational types. These data make this collection the second in importance for this group of insects in Mexico.